1672-1714 Conn. Acts 3 - (:unkn) unknown (My University, 1714)
Prohibited falsely alarming the colony by firing any gun or guns, at any time between the shutting in the Evening or break of day. Violators fined five pounds or two months imprisonment, or other Corporal punishment.
Keywords: DISCHARGE